Stress and Skin: An Overview of Mind Body Therapies as a Treatment Strategy in Dermatology - Rachel Graubard; Ariadna Perez-Sanchez; Rajani Katta (Mattioli1885, 2021)
Stress has multiple and wide-ranging physiologic and clinical impacts on skin disease. This has led to an interest in mind body therapies as potential adjunct treatments for skin disease. The stress response results in the activation of the endocrine, neurologic, and immune systems, with a resulting cascade of impacts, that are both systemic and cutaneous. The 2 main arms of the stress response are the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis. The resultant release of cortisol, catecholamines, and neuropeptides has multiple effects. Clinically, these have been shown to increase skin inflammation, increase itching, impair skin barrier function, impair wound healing, and suppress immunity. Mind body therapies are those that focus on the interaction between the mind and the body, with the goal to influence physical function and impact health. These have been shown to ameliorate some of the harmful physiologic changes attributed to stress or to reduce harmful behaviors. In some cases, such as with biofeedback, they may also result in beneficial physiologic changes. Treatments such as meditation, biofeedback, hypnosis, guided imagery, and others have been evaluated in the treatment of skin disease and have shown some benefits. Although randomized controlled trials are limited, these interventions have shown beneficial effects on itching, psychosocial outcomes, and even skin severity. These interventions have been evaluated in diseases such as atopic dermatitis, psoriasis, trichotillomania, and others. Given the potential benefits, improvements in psychosocial outcomes, and a low risk profile, referral to qualified practitioners or multidisciplinary clinics should be considered for some patients.